Self-medication among university students in Guangdong province, China: a cross-sectional study using the KAP model - Tan, Lu; Chen, Yuting; Gu, Meiling; Zhu, Jiangwei; Tang, Xiaoyan; Chen, Wenying; Feng, Huancun (Frontiers in Public Health, 2025)
ObjectiveSelf-medication has emerged as a significant global public health concern. Despite possessing a certain level of medication knowledge, university students in China exhibit a high-risk profile regarding self-medication practices. This study aimed to systematically investigate the current status and influencing factors of self-medication among university students in Guangdong Province, China, thereby providing evidence-based recommendations for targeted intervention strategies.MethodsA cross-sectional study was conducted based on the Knowledge-Attitude-Practice (KAP) model. Data were collected via anonymous questionnaire surveys distributed to university students in Guangdong Province, China. A total of 816 valid responses were analyzed. The questionnaire assessed demographic characteristics along with dimensions of medication knowledge, attitudes, and practices. Multiple linear regression analyses were subsequently performed to evaluate the impact of demographic factors on each dimension of the KAP model.ResultsStudents demonstrated a relatively high overall qualification rate in medication knowledge (93.50%), with 43.38% achieving a “Good” level and 50.12% rated as “Fair.” However, noticeable deficiencies were identified in attitudes and practices, with qualification rates approximately 75% in both dimensions. Notably, only 6.50% achieved a “Good” level in medication practices, while a substantial proportion (24.26%) was rated as “Unqualified.” Regression analyses revealed that age, current academic stage, and study mode significantly influenced medication knowledge scores. No significant demographic factors were associated with medication attitudes. However, age and the primary source of medication information significantly impacted self-medication practices. These findings offer empirical evidence essential for developing targeted medication safety education interventions among university students.ConclusionA clear discrepancy between knowledge and practice regarding self-medication exists among university students in Guangdong Province, China. Comprehensive intervention strategies are therefore, urgently required to promote rational medication behaviors within this population.